Shareholding Network in the Euro Area Banking Market - Nicolò Pecora; Alessandro Spelta (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2014)
Analyzing the topological properties of the network of shareholding relationships among the Euro Area banks we evaluate the relevance of a bank in the ?nancial system respect to ownership and control of other banks. We ?nd that the degree distribution of the European banking network displays power laws in both the binary and the weighted case. We also ?nd that the exponents are linked by a scaling relation revealing a direct connection between an increase of control diversi?cation and an increase of market power. Results also reveal Single Supervisory Mechanism, recently introduced by the European Central Bank and based on banks? total assets is a good proxy for the systemic risk associated to a particular ?nancial institution. Moreover we study how control and wealth are structured and concentrated within the banking system. Interestingly, our analysis reveals that control is highly concentrated at banking level, namely, lying in the hands of very few important shareholders that have weak relationships between them. This means that each main holder controls approximately a separate subset of banks.
Keywords: D85; E58; L14; 330; Shareholding network; European banking system; Weighted graph; Power law